Design of a Catfish Feeding Control System and Water Temperature Monitoring Based Internet of Things (IoT) - Firdausi, M. Faiz; Hermansyah, Mas’ud (IMPOWERMENT SOCIETY, 2023)
Catfish (Clarias gariepinus) is the main commodity and prima donna in the freshwater fish market which also generates significant sales in the market. Data from the Directorate General of Aquaculture from 2009 to 2013 shows an increase in consumption of catfish in Indonesia. From these data it can be seen that there is an economic potential from the needs of catfish in the market. To support meeting the needs of catfish, it is necessary to make efforts to increase catfish production, one of which is by increasing the work efficiency of catfish farming and monitoring water quality. Feeding automatically using a microcontroller is one way to increase work efficiency. This effort is realized in a design of an automatic catfish feeding device whose operating method uses the Internet of Things (IoT) concept to adjust the opening and closing of the feed door. The feeding algorithm or program is stored in the microcontroller (NodeMCU esp8266) as the control unit. The results of the application of the tool show that in terms of quality, automatic fish feeders can improve efficiency in feeding fish. In this case, the farmer's workload can be reduced for feeding activities. It is hoped that reducing the burden and working hours of farmers will provide opportunities for other productive activities for farmers.